Mortality of patients with severe COVID-19 during mechanical ventilation in an intensive care unit of a general hospital in Lima - Fernández Merjildo, Diana (2022)
Objective: To report on mortality and therapeutic interventions of patients with severe COVID-19 on mechanical ventilation in an intensive care unit (ICU). Methods: A retrospective cohort study of 105 patients with severe COVID-19 admitted to the ICU with respiratory failure needing mechanical ventilation from march to October 2020 was carried-out. Results: overall mortality of patients on mechanical ventilation was 38%; 79% were males: mean age was 49.8 ± 13 years; 65% did not have comorbidities; APACHE II score was 12±6; and the SOFA score was 5±3. Patients presented with lymphopenia, high serum levels of ferritin, lactic dehydrogenase and C-reactive protein. Thirty percent received hydroxychloroquine, 32% received azithromycin, 47% ceftriaxone and 27% received hydroxychloroquine plus azithromycin. Mortality was significantly higher in males (p=0,004), with high APACHE II (p=0.005) and high SOFA (p=0.0009) scores and with use of hydroxychloroquine (p=0,001), azithromycin (p=0.03) and both hydroxychloroquine plus azithromycin (p=0.001), no difference was observed with the use of steroids and ivermectin. Conclusions: The mortality of patients with severe COVID-19 admitted to the ICU on mechanical ventilation was higher in males and in those who received hydroxychloroquine, azithromycin or hydroxychloroquine plus azithromycin.